2011
DOI: 10.1039/c1sm05483j
|View full text |Cite
|
Sign up to set email alerts
|

Long-term in situ observation of barnacle growth on soft substrates with different elasticity and wettability

Abstract: In this paper, settlement, metamorphosis, and long term growth of barnacle on soft substrates with a wide elasticity range (modulus 0.01-0.47 MPa) as well as with the variation of wettability were investigated for the first time in vitro, in the laboratory environment. Tough double-network (DN) hydrogels and polydimethylsiloxane (PDMS) were used as the soft hydrophilic substrates and hydrophobic substrates, respectively, and polystyrene (PS), a hard and hydrophobic substrate, was used as a control. It was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…The settlement of larvae of F. enigmaticus was not significantly different on the three surfaces, polystyrene, PDMSe and glass (at 24 h, H = 3.228, p = 0.1991, at 48 h, H = 3.485, p = 0.175, Figure 5). This result is intriguing as typically the settlement of fouling organisms is lower on PDMSe than on polystyrene, eg settlement of day-7 cyprids of B. amphitrite was much lower on PDMSe (2-29%) than on the polystyrene (43%; Ahmed et al 2011). Ahmed et al (2011) found that the hydrophobic or hydrophilic properties of surfaces had no influence on the settlement of cyprids of B. amphitrite.…”
Section: Settlement Assaysmentioning
confidence: 81%
See 1 more Smart Citation
“…The settlement of larvae of F. enigmaticus was not significantly different on the three surfaces, polystyrene, PDMSe and glass (at 24 h, H = 3.228, p = 0.1991, at 48 h, H = 3.485, p = 0.175, Figure 5). This result is intriguing as typically the settlement of fouling organisms is lower on PDMSe than on polystyrene, eg settlement of day-7 cyprids of B. amphitrite was much lower on PDMSe (2-29%) than on the polystyrene (43%; Ahmed et al 2011). Ahmed et al (2011) found that the hydrophobic or hydrophilic properties of surfaces had no influence on the settlement of cyprids of B. amphitrite.…”
Section: Settlement Assaysmentioning
confidence: 81%
“…This result is intriguing as typically the settlement of fouling organisms is lower on PDMSe than on polystyrene, eg settlement of day-7 cyprids of B. amphitrite was much lower on PDMSe (2-29%) than on the polystyrene (43%; Ahmed et al 2011). Ahmed et al (2011) found that the hydrophobic or hydrophilic properties of surfaces had no influence on the settlement of cyprids of B. amphitrite. The settlement of cypris larvae of this species appears to respond to surface charge rather than total surface energy (Petrone et al 2011).…”
Section: Settlement Assaysmentioning
confidence: 81%
“…Such structures are reproduced as 3-dimensional patterned surfaces fabricated from synthetic polymers (e.g. Murosaki et al 2009, Aldred et al 2010bAhmed et al 2011;Greco et al 2013;del Campo 2013). Using such surfaces, Aldred et al (2010b) demonstrated similar effects on the settlement of cyprids of B. amphitrite as had been observed previously for B. improvisus.…”
Section: Introductionmentioning
confidence: 99%
“…(2) the growth rate of barnacles on both DN gels and PDMSs did not show a dependence on the elasticity of the soft substrata, but it showed a slightly higher value on the hydrophobic PDMS than on the hydrophilic DN gels; (3) the growth rate on these soft substrata was lower than that on the rigid PS substratum at a late stage of growth; (4) the 'release' of barnacles was observed from the PDMS substratum with a modulus higher than 0.01 MPa (Ahmed et al 2011).…”
Section: Introductionmentioning
confidence: 85%
“…In a previous paper (Ahmed et al 2011), a long-term (half year) laboratory assay of barnacles on soft substrata of PDMS and PAMPS/PAAm double network (DN) *Corresponding author. Email: gong@mail.sci.hokudai.ac.jp hydrogels was reported.…”
Section: Introductionmentioning
confidence: 99%